METHODOLOGY FOR MODELING THE INTEGRATED CONTENT OF CONTINUOUS SPECIALIZED EDUCATION ON THE BASIS OF INNOVATIVE DEVELOPMENT (American Journal of Pedagogical and Educational Research, 2026)
This article scientifically substantiates the methodology for modeling the integrated content of Continuous Specialized Vocational Education (CSVE) based on innovative development. The study defines the general concept of innovative processes, innovative competence, and innovative module, and classifies four categories of innovations: organizational, content-related, technological, and pedagogical. The goals and stages of operational design of integrative content, seven main functions of professional practice, and the mechanism for step-by-step formation of innovative competencies are described in detail. Scientific substantiation and consistent application of the methodology ensures the formation of all types of competencies - general cultural, general professional, and special professional competencies - thereby preparing well-rounded and adaptable graduates for the demands of the contemporary knowledge economy.